(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Chronic lymphocytic leukemia (CLL) is a malignancy of mature B cells. The genetic factors have been found to play a role in the pathogenesis of the disease. Deletions of the long arm of chromosome 13, specifically involving band 13q14 (del(13q14)) constitute the single most frequently observed cytogenetic aberration in CLL, occurring in 55% of all cases, followed by structural abnormalities of ch 12(trisomy 12), del 11q22.3-q23.1, del 6q21-q23, del 17p13.1, and 14q. Objective: To detect frequencies of chromosome 13q14 deletion, chromosome 11q22 deletion and trisomy 12 in in CLL patients using FISH technique, and to investigate the relation between those chromosomal abnormalities and clinical features and hematological parameters. Methods: This cross-sectional study was conducted on fifty newly diagnosed patients with CLL. Three ml of fresh blood were taken from each patient at admission and then transfer it to FISH unit for blood preparation. Slide preparation was done by using dual color fusion gene probe. The slides were read in the second day by fluorescent microscope. Results: Deleted chromosome 13 was found in 24 out of 50 patients, (48%). Trisomy chromosome 12 was found in 15 out of 50 patients, (30%). Deleted chromosome 11 was found in 12 out of 50 patients, (24%). Conclusion: In a sample of Iraqi adult with CLL, the most frequent chromosomal abnormality was deletion of chromosome 13 followed by trisomy of chromosome 12 and chromosome 11 deletion. Keywords: Chronic lymphocytic leukemia, FISH, deleted chromosome 13, trisomy chromosome 12 Citation: Hashim HH, Abdulateef SS. Detection of chromosome 13q14 deletion, chromosome 11q22 deletion and trisomy 12 in chronic lymphocytic leukemia patients. Iraqi JMS. 2021; 19(2): 213-229. doi: 10.22578/IJMS.19.2.11